Effect of the Coadministration of Daclatasvir on the Pharmacokinetics of a Combined Oral Contraceptive Containing Ethinyl Estradiol and Norgestimate. Issue 5 (July 2014) - Bifano, Marc; Sevinsky, Heather; Hwang, Carey; Kandoussi, Hamza; Jiang, Hao; Grasela, Dennis; Bertz, Richard
Background: Daclatasvir is a highly selective NS5A replication complex inhibitor currently in development for the treatment of chronic hepatitis C infection. Daclatasvir is active at picomolar concentrations and demonstrates in vitro activity against a broad range of HCV genotypes. The primary objective of this study was to assess the effect of daclatasvir on the pharmacokinetics of a combined oral contraceptive containing ethinyl estradiol and norgestimate (Ortho Tri-Cyclen®). Methods: In this open-label single-sequence study, 20 healthy female subjects received ethinyl estradiol and norgestimate for three cycles, with coadministration of daclatasvir in cycle 3. Pharmacokinetics of ethinyl estradiol and the active metabolites of norgestimate (norelgestromin and norgestrel) were assessed in cycles 2 and 3. Results: Adjusted ratios of geometric means and 90% CIs were estimated for the maximum observed plasma concentration (ethinyl estradiol 1.11 [1.02, 1.20], norelgestromin 1.06 [0.99, 1.14] and norgestrel 1.07 [0.99, 1.16]) and area under the plasma concentration–time curve in one dosing interval (ethinyl estradiol 1.01 [0.95, 1.07], norelgestromin 1.12 [1.06, 1.17] and norgestrel 1.12 [1.02, 1.23]). Conclusions: Coadministration of daclatasvir resulted in no clinically relevant effects on exposure to ethinyl estradiol, norelgestromin or norgestrel.